Frenetic, Underchallenged, and Worn-Out: Validation of the German “Burnout Clinical Subtypes Questionnaire”—Student Survey and Exploration of Three Burnout Risk Groups in University Students - Bauernhofer, Kathrin; Tanzer, Norbert; Paechter, Manuela; Papousek, Ilona; Fink, Andreas; Weiss, Elisabeth M. (Frontiers in Education, 2019)
Against the background of inconsistent findings regarding the symptomatology, etiology, and risk factors of burnout, Farber (1990) proposed three different burnout subtypes: frenetic, underchallenged, and worn-out. Montero-Marín and colleagues (2011) expanded the typology to the academic context and developed the Burnout Clinical Subtypes Questionnaire–Student Survey (BCSQ-12-SS) to examine whether three burnout risk groups, that are in line with the typology, exist in university students as well. However, due to a moderate overlap between the BCSQ-12-SS subscales describing different risk groups, it has remained unclear whether three burnout risk groups can indeed be distinguished in university students. Moreover, the BCSQ-12-SS is currently not available in German, limiting the possibility to examine the typology in different student populations. Therefore, the aim of this study was to validate the BCSQ-12-SS for German speaking university students and to investigate whether three burnout risk groups—frenetic, underchallenged, and worn-out—can be identified in students using a person-oriented approach. Overall, 404 German speaking university students were recruited and filled in several online questionnaires, including the Maslach Burnout Inventory–Student Survey (MBI-SS) and the BCSQ-12-SS that was translated to German for the purpose of this study. The German BCSQ-12-SS had good psychometric properties. Latent profile analysis (LPA) with the BCSQ-12-SS distinguished three burnout risk groups: frenetic, underchallenged, and worn-out students, whereby mildly and severely worn-out students could be differentiated. Additionally, a group with healthy engaged students emerged. The groups differed in burnout symptoms, feelings of depression, workload, study engagement, and academic resources. Furthermore, the burnout risk groups could also be distinguished in a subsample of students (n=150) who are particularly vulnerable to develop burnout because they were all moderately to highly stressed. LPA with the MBI-SS resulted in profiles similar to the healthy engaged, frenetic and severely worn-out profile. However, an underchallenged profile was only discovered with the BCSQ-12-SS, indicating that this questionnaire is particularly useful to detect an additional burnout risk group that has widely been overlooked in student burnout research so far. Taken together, this study observed three burnout risk groups in German speaking university students: frenetic, underchallenged, and worn-out.